The intertemporal dynamic relationship between the level and variability of food price inflation: evidence from sri lankan economy - Sivarajasingham, S.; Balamurali, N. (University of Jaffna, 2018)
This study examines the intertemporal dynamic linkages between food price inflation and its volatility. FIGARCH model is employed to estimate conditional volatlity of food price inflation. The empirical evidence derived from the monthly data for the period from 2003M1 to 2016M12 for Sri Lanka. Granger causality tests show that food inflation seems to exert positive impact on inflation uncertainty. Hence, the findings of the study supports the Friedman hypothesis. This implies that past information on food inflation can help improve the one step-ahead prediction of food inflation uncertainty but not vice versa. In addition, our study show that volatility of CFPI inflation also Granger causes the volatility of WFPI inflation. Our results have some important policy implications for the design of monetary policy, thereby promoting macroeconomic stability. In particular, the results indicate the importance of inflation stablization programmes.
Keywords: Food inflation; Inflation uncertainty; FIGARCH; Causality